Hydrocarbon Reservoir Evaluation and Fault Seal Analysis of Balkassar Area, Potwar Sub Basin, Pakistan - Shakir, U.; Abbas, M.; Ahmad, W.; Mahmood, M. F.; Hussain, M.; Anwar, M.; Sikandar, U.; Naseem, T. (The Nucleus, 2020)
Balkassar oilfield is one of the major hydrocarbon producing field in Potwar Plateau, Upper Indus Basin, Pakistan. This field has been producing oil and gas from fractured carbonate deposits of Eocene and Paleocene age. So, in order to delineate the hydrocarbon potential of the Balkassar area, 2D seismic interpretation and petrophysical analysis has been carried out and is represented in the current study using five seismic lines and one well. Balkassar field is geographically located in central part of Potwar Sub-basin. Geologically it is located in Himalayan foreland fold and thrust belt, which is dominated by thrusting and folding features. The salt tectonics is responsible for the formation of structural traps in Balkassar area. The direction of deformation is in NW- SE direction. The main reservoir formations of Balkassar area are Chorgali Formation and Sakesar Limestone which are charged by shales of Patala Formation of Paleocene age. Formations were identified on the seismic section on the basis of timedepth chart and well tops. Petroleum trap is a structural trap where major thrust and back thrust bound the anticline, and sealing impact is provided by both clays of Murree Formation and faults which is further confirmed through fault seal analysis (Allan diagram). One reservoir zone has been identified in Chorgali Formation using petrophysical analysis, which indicates effective porosity of 3.08%, 40.5% water saturation and 59.5% hydrocarbon saturation. Based on the statistical analysis performed, it is concluded that the Chorgali Formation is more economically promising as compared to Sakesar Limestone. Volumetric reserves calculation is done to estimate the volume of original oil in place (OOIP) for the Chorgali Formation, which comes out to be 18.6 Million Barrels for P90 case.